Comparison between Conditioned Pain Modulation Paradigms Using Cold Pressor Conditioning Stimulus versus Ischemic Pressure Stimulus in Women with Fibromyalgia and Its Impact on Clinical Status: A Cross-Sectional Study - Víctor Riquelme-Aguado; María Elena González-Álvarez; Alazne Zabarte-Del Campo; Josué Fernández-Carnero; Antonio Gil-Crujera; Francisco Gómez-Esquer; Jorge Hugo Villafañe (Biomedicines, 2024)
Background/Objectives: Fibromyalgia (FM) is a syndrome characterized by widespread chronic pain as the primary symptom. Neurophysiological pain mechanisms, such as the function of the descending inhibitory system, are impaired in this condition. The main objective of this study was to compare the results of two paradigms to evaluate CPM in women with FM. The secondary objective was to correlate the results of each CPM paradigm with the clinical status of patients with FM. Methods: One hundred and three FM women were divided into two groups: fifty patients diagnosed with FM were assigned to the conditioned pain modulation (CPM) group using a cold pressor stimulus, and fifty-three patients were assigned to the CPM group using the ischemic pressure stimulus. The main outcome measures were pain intensity, disability, mechanical hyperalgesia, and CPM. Results: The primary analysis revealed significant differences between the results obtained from the different CPM protocols. Poorer outcomes in the cold pressor test correlated with higher pain intensity and a greater disability index. Conclusions: Pain modulation abnormalities in FM patients were evident when using either the cold pressor or ischemic pressure stimuli to establish the CPM paradigm. The cold pressor conditioning stimulus elicited a stronger response than the ischemic pressure stimulus in FM patients.